2009
DOI: 10.1097/bpb.0b013e32832dbeb4
|View full text |Cite
|
Sign up to set email alerts
|

Severe hip infection after a prophylactic contralateral fixation in slipped upper femoral epiphysis: a case report

Abstract: The rate of infection is extremely low after a prophylactic contralateral fixation in slipped upper femoral epiphysis, and exclusively involves superficial wound infection. We report an unusual case of hip infection after a prophylactic pinning with a single cannulated screw. The evolution was unfavorable, with necrosis and epiphysiolysis of the femoral head. A total hip arthroplasty was performed after 1 year of evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Studies have suggested an in situ pinning of a normal hip as a result of a higher slipping rate (2335 times) than that of a normal hip [ 17 ]. In contrast, other authors have argued against prophylactic pinning for the unaffected hip due to the exposure of the normal hip to surgical pinning, which could damage the joint, thereby resulting in further exposure of the patient to surgical risks such as infection, fracture, pain, avascular necrosis, and chondrolysis [ 18 ]. An analysis of some of the cases revealed devastating deleterious effects of the complications, with some of the cases advocating for non-surgical intervention in managing an unaffected hip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested an in situ pinning of a normal hip as a result of a higher slipping rate (2335 times) than that of a normal hip [ 17 ]. In contrast, other authors have argued against prophylactic pinning for the unaffected hip due to the exposure of the normal hip to surgical pinning, which could damage the joint, thereby resulting in further exposure of the patient to surgical risks such as infection, fracture, pain, avascular necrosis, and chondrolysis [ 18 ]. An analysis of some of the cases revealed devastating deleterious effects of the complications, with some of the cases advocating for non-surgical intervention in managing an unaffected hip.…”
Section: Discussionmentioning
confidence: 99%
“…Other categories of SUFE classification are acute, acute-on-chronic, and chronic. A SUFE is regarded as acute if symptoms are present for less than three weeks, while the acute-on-chronic hip occurs upon exacerbation of the symptoms in an asymptomatic hip, which may result in complications such as chondrolysis, secondary osteoarthritis, and avascular necrosis [ 18 - 20 ]. The current study revealed only two acute cases, both of which were associated with trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Since pinning of a normal hip is not free from complications, it is essential to identify the patients at the risk of subsequent contralateral slip development and recommend prophylactic pinning of the contralateral hips. [6] There is no consensus in risk evaluation, and it is commonly made according to patients' radiological parameters that evaluate growth potential. [7][8][9] In this study, we aimed to compare the radiological parameters of unilateral SCFE patients who reached skeletal maturity without developing subsequent contralateral slips and unilateral SCFE patients who developed subsequent contralateral slips.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 Moreover, prophylactic surgery may predispose toward certain complications, such as: infection, implant breakage, avascular necrosis, chondrolysis or subtrochanteric fracturing of the femur. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%